Multiculturalism and nation-building - a South Indian perspective - Jayaram, N. (2000)
Viewing the ideology of `multiculturalism' as a reaction to the metamorphosis of `nationalism,' this paper addresses some issues in national integration and nation-building emerging from the interface between the two in south India. While the specific issues dealt with relate to the four states of Andhra Pradesh, Karnataka, Kerala and Tamil Nadu, the emergent highlights are sought to be placed in the pan-Indian context. - Reproduced
Keywords: Multiculturalism - South India; Nation building - South India; Nationalism - South India; Nationalism